An exploration into a new theoretical perspective of firm growth: Combining resources, mediating factors and output factors - Samantha Burvill (British Academy of Management, 2015)
Theoretical development within the firm growth literature has been noticeably limited since the generation of Penrose’s (1959) theory of the growth of the firm. Since then the resource based view of the firm has been widely studied and debated and yet is criticised for being too vague. This paper reviews the resource based view of the firm and undertakes empirical grounded theory research, in an attempt to identify the key resources required for firm growth to occur. The research resulted not only in the generation of key resources but in the generation of a new firm growth theory, explaining how resources interact with other areas of the firm to enable firm growth. Conclusions are made regarding the implications of the findings for future research.